Additive‐Induced Synergies of Defect Passivation and Energetic Modification toward Highly Efficient Perovskite Solar Cells. Issue 29 (17th June 2021) - Xiong, Shaobing; Hou, Zhangyu; Dong, Wei; Li, Danqin; Yang, Jianming; Bai, Ruirong; Wu, Yuning; Li, Dong; Wu, Hongbo; Ma, Zaifei; Xu, Jianhua; Liu, Xianjie; et al.
Abstract: Defect passivation via additive and energetic modification via interface engineering are two effective strategies for achieving high‐performance perovskite solar cells (PSCs). Here, the synergies of pentafluorophenyl acrylate when used as additive, in which it not only passivates surface defect states but also simultaneously modifies the energetics at the perovskite/Spiro‐OMeTAD interface to promote charge transport, are shown. The additive‐induced synergy effect significantly suppresses both defect‐assisted recombination and interface carrier recombination, resulting in a device efficiency of 22.42% and an open‐circuit voltage of 1.193 V with excellent device stability. The two photovoltaic parameters are among the highest values for polycrystalline CsFormamidinium/Methylammonium (FAMA)/FAMA based n‐i‐p structural PSCs using low‐cost silver electrodes reported to date. The findings provide a promising approach by choosing the dual functional additive to enhance efficiency and stability of PSCs. Abstract : Additive‐induced synergies of defect passivation and energetic modification in perovskite solar cells are investigated, which boost power conversion efficiency and stability of the devices.